Kawasaki disease with three recurrences. A case report - Luis Martín Garrido-García; Nadia Mata-Favela; Marco Antonio Yamasaki-Nakashimida (Instituto Nacional de Pediatría, 2014)
Kawasaki disease is a systemic vasculitis of unknown origin predomi- nantly affecting children under the age of 5 years. Is the most common cause of acquired cardiac disease in developed countries. We don't know the epidemiology in Mexico because there are only few reports of the disease. Recurrence of the disease has been reported in approxi- mately 3% of all cases and second recurrences are rarer. We present the case of a patient with Kawasaki disease with 3 recurrences who developed transient coronary artery lesions in 2 of these events.